Comparative Law and Reflections on the Progressive Closing of Mining Projects in Colombia and Peru - Peña Moreno, Efraín (2014)
The objective of this article is to present the importance of implementing the Closure Planfor Mineral Projects. To this purpose, the author studies and analyzes success stories of closing mining projects, in particular, focuses its analysis on Colombian and Peruvian cases.